A systematic review of social support in youth sport - Sheridan, D.; Coffee, P.; Lavallee, D. (International Review of Sport and Exercise Psychology, 2014)
The purpose of this study was to provide a systematic review of studies concerning social support in youth sport from 1990 to 2013. A total of 73 studies were evaluated and are reported in four sections: sample characteristics; research designs; social support provider type; and key correlates relating to social support. Samples ranged from 1 to 564. Studies examined a wide range of sports, ages (10-22 years) and competition levels. Studies used qualitative (23%), quantitative (75%) and mixed-model (2%) designs. The main conclusion is that recent advances in the conceptualization of social support have generated a more diverse set of methods to examine the quantity and satisfaction of social support in a sports context. Coaches were identified as the most prevalent provider of social support through offering participants unique forms of tangible, informational, emotional and esteem support. Furthermore, coach, parent and peer support plays a significant role in shaping youth sport experiences both from a positive (athlete motivation levels, elite sport participation) and negative (drop-out) perspective. The discussion focuses on the current status of the research area, limitations, suggested practical implications (e.g., providing proactive support) and future research directions (e.g., examining optimal support matching).